Daya Hambat Bakteri Lactobacillus plantarum JBS4 Asal Fermentasi Tigarun Terhadap Bakteri Patogen - Fasha, Gusti Nur Aida; Rahmi, Nazarni; Nur, Hasrul Satria (Universitas Negeri Gorontalo, 2025)
Lactobacillus plantarum JBS4 is a lactic acid bacterium isolated from the fermentation of tigarun (Crataeva nurvala Buch.-Ham) with potential antimicrobial activity. This study aimed to evaluate the inhibitory effect of Lac. plantarum JBS4 against pathogenic bacteria Escherichia coli ATCC25922 and Staphylococcus aureus ATCC25923 in vitro. The inhibition test was conducted using the well diffusion method on NA and MRS agar media. The results showed that Lac. plantarum JBS4 effectively inhibited the growth of E. coli and S. aureus, with inhibition zone diameters of 9.10 ± 0.08 mm and 9.32 ± 0.29 mm, respectively. Furthermore, this isolate did not exhibit inhibitory effects against Lactobacillus acidophilus FNCC0051, a nonpathogenic bacterium. These findings suggest that Lac. plantarum JBS4 has the potential to act as a selective antimicrobial agent against pathogenic bacteria without affecting beneficial microorganisms.